ANALISIS PERAN FUNGSI PENGENDALIAN INTERNAL PADA KETERLAMBATAN PEMBAYARAN ORDERAN BARANG PADA PT. MEDIKON PRIMA LABORATORIES - Jayida Syifa, Naila; Ahmad Hasibuan, Nur Fadhilah (LP2M Universitas Bina Bangsa, 2025)
This study analyzes the role of the internal control function in overcoming delays in payment of goods orders at PT Medikon Prima Laboratories. Late payments are the main obstacle that affects the company's operational efficiency and financial stability. With a qualitative approach, this study evaluates various aspects of internal control, such as preventive, detective, and corrective functions, to identify the root cause of problems and provide strategic solutions. The results show that strong internal control is able to mitigate risks, increase efficiency, and strengthen stakeholder trust. The main conclusion highlights the importance of applying information technology and improving staff training to improve the company's financial management process.